2019
DOI: 10.1002/jmd2.12033
|View full text |Cite
|
Sign up to set email alerts
|

Survey of quality of life, phenotypic expression, and response to treatment in Krabbe leukodystrophy

Abstract: Objectives To develop a quality of life (QOL) survey for Krabbe disease (KD), and to thereby improve understanding of its phenotypic expression and response to treatment. Methods The survey, the Leukodystrophy Quality of Life Assessment (LQLA) and the Vineland Adaptive Behavior Scales were co‐administered to 33 patients or their caretakers. These included the phenotypes of early infantile KD (EIKD; 0‐6 months old at onset), late infantile cases (LIKD; 7‐12 months old at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…A mother mentioned concerns about the patient's relationships with others. Studies on Krabbe disease, a leukodystrophy similar to MLD, have shown a negative impact of the severe type with infantile onset on communication and school attendance [ 26 ]. Moreover, the burden of getting patients out of the house increases as their disability progresses, and they require suction and ventilators.…”
Section: Discussionmentioning
confidence: 99%
“…A mother mentioned concerns about the patient's relationships with others. Studies on Krabbe disease, a leukodystrophy similar to MLD, have shown a negative impact of the severe type with infantile onset on communication and school attendance [ 26 ]. Moreover, the burden of getting patients out of the house increases as their disability progresses, and they require suction and ventilators.…”
Section: Discussionmentioning
confidence: 99%
“…In a quantitative study that determined the impact of leukodystrophy on patients’ QOL, a disease-specific QOL scale for patients with Krabbe disease was developed. 14 Another study found that mothers of patients with MLD have a lower QOL than the general population. 15 It is important to interpret the experiences of patients and their families to identify the impact and challenges of the disease on their lives.…”
Section: Introductionmentioning
confidence: 99%
“…Few quantitative studies have focused on the quality of life (QOL) of patients with MLD, ALD, or Krabbe disease and their family members. In a quantitative study that determined the impact of leukodystrophy on patients’ QOL, a disease-specific QOL scale for patients with Krabbe disease was developed 14 . Another study found that mothers of patients with MLD have a lower QOL than the general population 15 .…”
Section: Introductionmentioning
confidence: 99%
“…3 In a quantitative study that determined the impact of leukodystrophy on patients' quality of life (QOL), a disease-specific QOL scale for patients with Krabbe disease was developed. 14 A study focusing on the QOL of family member of patients with MLD reported that family members, and particularly mothers, have a lower QOL than the general population. 15 However, since these diseases are rare, insufficient quantitative studies have focused on the QOL of patients and their family members.…”
Section: Introductionmentioning
confidence: 99%